Fatal venous air embolism in swine during surgical procedure - KATSIMPOULAS, M; KAKISIS, I; PEROULIS, M; DIMITRIOU, K; BALAFAS, E; KOSTOMITSOPOULOS, N (Journal of the Hellenic Veterinary Medical Society, 2018)
Air embolism can occur after minor invasive procedures, as well as during major surgical operations. Reports of air embolism cases in veterinary literature are not very often, although it is considered that it happens more often than it is recognized. During a surgical procedure in swine, for the creation of a fistula of PTFE graft between the right common carotid artery and the right jugular vein under general anaesthesia, the animal died due to massive venous air embolism. Although it is supposed that the air was possibly inserted through the anaesthetic machine or through the anastomosis, the exact mechanism of the air insertion remains unknown.